Representasi Degradasi Keimanan dalam Cerpen “Wabah” Karya Ahmad Mustofa Bisri - Arif Rahman; Tristanti Apriyani (Badan Pengembangan dan Pembinaan Bahasa, 2024)
A decline in one's faith may result from a lack of literacy or knowledge about the ethical principles associated with transcendence. It is of significant importance to enhance the literacy about transcendence, with the objective of elevating the quality of religious individuals. This study aims to elucidate the phenomenon of the degradation of faith as depicted in the short story